Complex serials and episodic flexi-narratives: narrative extension in the transmedia storytelling of heroes and supernatural - Wisher, Emma Lauren (2017)
This thesis provides a comparative analysis of Heroes (2006-2010) and Supernatural (2005-Present) to argue that television narrative structure influences the transmedia narrative formed. Many television narratives use transmedia storytelling to develop plotlines and characters without intruding upon the television episodes. The interconnectivity of the transmedia texts with the main narrative determines which transmedia narrative is formed. Single-world transmedia narratives create complex, connected worlds like a television serial whilst possible-world transmedia narratives are constructed from self-contained stories like an episodic series. Heroes and Supernatural exemplify the differences between narrative extension in single-world and possible-world transmedia narratives, both within the transmedia texts and the television episodes. I argue that world components, temporality and character development are extended differently in television serials and flexi-narratives, and can determine whether a transmedia text’s relationship with the television narrative is consistent or implied. My ideas can be applied to narrative extension in other transmedia television narratives, creating a framework that identifies whether a single-world or possible-world is formed.